Association of the gut microbiome with kidney function and damage in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). (31st December 2023) - Peters, Brandilyn A.; Qi, Qibin; Usyk, Mykhaylo; Daviglus, Martha L.; Cai, Jianwen; Franceschini, Nora; Lash, James P.; Gellman, Marc D.; Yu, Bing; Boerwinkle, Eric; Knight, Rob; Burk, Robert D.; et al.
ABSTRACT: Background: The gut microbiome is altered in chronic kidney disease (CKD), potentially contributing to CKD progression and co-morbidities, but population-based studies of the gut microbiome across a wide range of kidney function and damage are lacking. Methods: In the Hispanic Community Health Study/Study of Latinos, gut microbiome was assessed by shotgun sequencing of stool ( n  = 2, 438; 292 with suspected CKD). We examined cross-sectional associations of estimated glomerular filtration rate (eGFR), urinary albumin:creatinine (UAC) ratio, and CKD with gut microbiome features. Kidney trait-related microbiome features were interrogated for correlation with serum metabolites ( n  = 700), and associations of microbiome-related serum metabolites with kidney trait progression were examined in a prospective analysis ( n  = 3, 635). Results: Higher eGFR was associated with overall gut microbiome composition, greater abundance of species from Prevotella, Faecalibacterium, Roseburia, and Eubacterium, and microbial functions related to synthesis of long-chain fatty acids and carbamoyl-phosphate. Higher UAC ratio and CKD were related to lower gut microbiome diversity and altered overall microbiome composition only in participants without diabetes. Microbiome features related to better kidney health were associated with many serum metabolites (e.g., higher indolepropionate, beta-cryptoxanthin; lower imidazole propionate, deoxycholic acids, p-cresol glucuronide). Imidazole propionate, deoxycholic acid metabolites, and p-cresol glucuronide were associated with prospective reductions in eGFR and/or increases in UAC ratio over ~6 y. Conclusions: Kidney function is a significant correlate of the gut microbiome, while the relationship of kidney damage with the gut microbiome depends on diabetes status. Gut microbiome metabolites may contribute to CKD progression.